A survey of current care for children and adults with osteogenesis imperfecta in Glasgow. (24th May 2012) - Narayanan, VK; Dougan, E; Duncan, R; Kinning, E; Gallacher, S; Gallagher, A; Galloway, P; Hinnie, J; Mclellan, A; Panarelli, M; Ahmed, SF
Abstract : Introduction: There are scarce reports of the clinical caseload and the provision of services for children and adults with osteogenesis imperfecta (OI). Aims: To perform a survey of the clinical characteristics of patients with a diagnosis of OI that attend metabolic bone and genetic clinics in the city of Glasgow Methods: Clinical details of 53 children (M:28) and 23 adults (M:9) were obtained by review of case records obtained from the Genetics and Occupational therapist lists. Results: The median age at presentation in children was 4.5 years (range 0.2-13.5), with 14/53 (26%) diagnosed within the first year. Of the 53 children, 33 (62%) had fracture onset within the first year, 17 between 1-5 years and 1 after 5 years. 34 (64%) had peak fracture frequency of 1-4 fractures per year with 4 (8%) having >5 fractures per year. Peak fracture occurrence was between 1-5 years (47%). Skeletal deformities were recorded in 23 children (43%) and 6 adults (26%). Pain was recorded as a problem in 31 (58%) children and 10 (43%) adults. Most patients were fully mobile; 6 children and 1 adult had very limited mobility. In children, input from occupational therapy, dentistry, orthopaedics, genetics, physiotherapy and pain team was recorded in 35 (66%), 34 (64%), 23 (43%), 14 (26%), 9 (17%) and 2 cases, respectively. DXA scan was performed in 48 (90%) children but the results were uninterpretable in 30%; 18 (78%) adults had DXA scans. Spinal XR were performed in 52/53 (98%) children with normal results in 13, compression fractures in 17 and spinal deformity 16. All 6 adults who had spinal XR had compression fractures. Serum Vitamin D was measured in 85% children and 74% adults with levels <50 nmol/l in 25 (47%) children, and 10 (43%) adults. 21 children and 12 adults were prescribed Vitamin D. Bisphosphonates were prescribed in 36 (68%) children and 11 (48%) adults. 8 (15%) children and 3 (13%) adults were recorded to have had orthopaedic interventions. Positive family history was recorded in 31 (58%) children and 17 (74%) adults. In 25/31 children and 11/17 adults with positive family history affected family members were offered appointments. Conclusion: OI is a rare, life-long, skeletal condition requiring multidisciplinary specialist input. There is a need to develop standards of care that can facilitate long-term care.